THE RELATIONSHIP BETWEEN INTERPERSONAL COMMUNICATION AND NARRATIVE WRITING MOTIVATION AMONG DPKU IPB CLASS OF 61 STUDENTS - Prayudhi, Risa; Ansori, Mukhlas; Indriani, Dewi (Jurnal Salaka : Jurnal Bahasa, Sastra, dan Budaya Indonesia, 2025)
This study aims to analyze the relationship between interpersonal communication and narrative writing motivation among DPKU IPB class of 61 students. The research employed a quantitative approach with a correlational design. The sampling technique used was purposive sampling, involving 100 students as respondents. Data were collected through a Likert-scale questionnaire, which had been tested for validity and reliability. The Kolmogorov-Smirnov normality test indicated that the data were normally distributed (p 0.05), allowing the use of the Pearson Product-Moment correlation for analysis. The results show a positive and significant relationship between interpersonal communication and narrative writing motivation, with a correlation coefficient (r) = 0.429 and a significance level (p 0.001). This correlation falls within the moderate category based on Cohen's guidelines. This finding implies that better interpersonal communication is associated with higher motivation for narrative writing. Based on these findings, it is recommended that students enhance their interpersonal communication skills through activities supporting social interaction. Educators are encouraged to create a communicative and supportive learning environment to foster students' writing motivation. Future research is suggested to explore other variables, such as social support or personal interest, that may also influence narrative writing motivation.